An efficient one-pot synthesis of substituted 2-aminobenzo-1-thiophene-3-carbonitriles. Issue 24 (10th June 2015) - Krishnananthan, Subramaniam; Smith, Daniel; Traeger, Sarah C.; Mathur, Arvind; Li, Jianqing
Graphical abstract: Abstract: An efficient one-pot synthesis of substituted 2-aminobenzo-1-thiophene-3-carbonitriles from substituted 2-(2-fluorophenyl)acetonitriles and O -ethyl carbonisothiocyanatidate in moderate to good yields was described.